O papel do Estado-membro no planejamento metropolitano diante do ordenamento jurídico urbanístico brasileiro - Almeida, Florisvaldo Cavalcante de (2013)
The object of this work is the role of the Member State in metropolitan planning before the legal system Brazilian urban. Broke from the premise that the entire state action must be provided, either implicitly or explicitly, in the Federal Constitution. Of initiation, it was examined whether, by making a logical interpretation-systemic of the constitutional text, pointing out the object of study of Urban Law, which constitutes a Right founder member of public policies, which needs the actuation of positive State for its implementation. Such action must give way if planned. With this, it was possible to determine that the planning is considered the main instrument for structuring of this branch of Law, whose competence has been assigned, by constitutional text, all the loved federative. All loved have a duty to deal with the urban planning, once that competence means a duty/power, a power linked to particular purpose. began to investigate the Metropolitan Region, institutional arrangement, whose creation has by immediate purpose establish a metropolitan planning integrated to deal of public functions of common interest. It has been detected that the ownership of these public functions is the Member State and of the Municipalities Regional members of the figure. Consequently, the preparation and execution of these functions should be given by these loved of shared form. It was concluded that it is incumbent upon the Member State, in addition to the creation of the Metropolitan Region, the organization, the planning and execution of public functions of common interest. It should ensure the participation of Municipalities that comprise the Regional figure and of civil society in the organization, planning and execution of public functions of common interest